SLC15A4 controls endolysosomal TLR7–9 responses by recruiting the innate immune adaptor TASL - Haobo Zhang; Léa Bernaleau; Maeva Delacrétaz; Ed Hasanovic; Ales Drobek; Hermann Eibel; Manuele Rebsamen (Cell Reports, 2023)
Summary: Endolysosomal Toll-like receptors (TLRs) play crucial roles in immune responses to pathogens, while aberrant activation of these pathways is associated with autoimmune diseases, including systemic lupus erythematosus (SLE). The endolysosomal solute carrier family 15 member 4 (SLC15A4) is required for TLR7/8/9-induced responses and disease development in SLE models. SLC15A4 has been proposed to affect TLR7–9 activation through its transport activity, as well as by assembling an IRF5-activating complex with TASL, but the relative contribution of these functions remains unclear. Here, we show that the essential role of SLC15A4 is to recruit TASL to endolysosomes, while its transport activity is dispensable when TASL is tethered to this compartment. Endolysosomal-localized TASL rescues TLR7–9-induced IRF5 activation as well as interferon β and cytokine production in SLC15A4-deficient cells. SLC15A4 acts as signaling scaffold, and this function is essential to control TLR7–9-mediated inflammatory responses. These findings support targeting the SLC15A4-TASL complex as a potential therapeutic strategy for SLE and related diseases.